Lesions of the Orbitofrontal but Not Medial Prefrontal Cortex Affect Cognitive Judgment Bias in Rats - Golebiowska, Joanna; Rygula, Rafal (Frontiers in Behavioral Neuroscience, 2017)
Neuroimaging studies in humans have recently shown that the prefrontal cortex (PFC) and orbitofrontal cortex (OFC) mediate bias in the judgement of forthcoming events. In the present study, we sought to determine whether cognitive judgement bias (CJB) is also dependent on these prefrontal regions in non-human animals. For this, we trained a cohort of rats in the ambiguous-cue interpretation (ACI) paradigm, subjected them to excitotoxic lesions in the medial PFC (mPFC) and OFC, and tested the effects of neuronal loss within these regions on CJB. Comparison of the lesions’ behavioural effects in the ACI paradigm revealed that neuronal loss within the OFC but not within the mPFC influences the interpretation of ambiguous cues by animals. Our findings demonstrate the specific involvement of the OFC in CJB in rats.